Outsourcing wywiadu gospodarczego w przedsiębiorstwie - Kwiecieński, Mirosław; Mielus, Magdalena (Outsorcing of competitive intelligence in an enterprise, 2006)
The main point of the presented paper concerns the outsourcings of economical intelligence. They support enterprises in the scope of rising, storage, processing and difussion of information. The authors show advantages and disadvantages of using competitive intelligence and economical information offices. In the further part of the paper possible applications of outsorcing as well as possible risk and the protection of the source of information are considered.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 141-148